PENGARUH KUALITAS AUDIT TERHADAP KINERJA PERUSAHAAN DENGAN KEPEMILIKAN INSTITUSIONAL SEBAGAI VARIABEL MODERATING - Yudi Tri Saputra; Agus Kubertein (Balance: Media Informasi Akuntansi dan Keuangan, 2023)
The Effect of Audit Quality on Company Performance with Institutional Ownership as a Moderating Variable (empirical study of banking sector companies listed on the Indonesia Stock Exchange (BEI) in 2016-2019) Thesis of Accounting Department, Faculty of Economics and Business. Under the guidance of Mrs. Dr. Fitria Husnatarina., SE., M.Si., Ak., CA and Mr. Agus Kubertein., SE., M.Si. This study aims to analyze the effect of Audit Quality on Company Performance and to analyze the effect of Audit Quality on Company Performance which is moderated by Institutional Ownership. The research method used in this study is a descriptive-quantitative research approach. The unit of analysis of this research is the banking sector companies listed on the Indonesia Stock Exchange (BEI), totaling 45 companies with non-probability sampling techniques and using purposive sampling. The collected data were analyzed using SPSS 24. The results showed that the quality of the audit has no effect on company performance, institutional ownership weakens the relationship between audit quality and company performance.